Nursing team: experience of care of children with cancer in night shifts - Melo, Luciana de Lione; Valle, Elizabeth Ranier Martins do (Revista da Escola de Enfermagem da USP, 1998)
The present study aimed understanding some aspects of the experience of a nursing team that take care of children with cancer in night shifts. Therefore, the author used a qualitative methodology - phenomenological method - that enabled her to analyse the declarations of the nursing team about their experience. The convergences of their speech were analysed and some units of meaning were identified in order to contribute to institutionally assure the necessary work conditions to the nursing personnel as well as to prepare the team to face these circumstances.